2014
DOI: 10.1002/maco.201307447
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of nickel‐containing weathering steel in simulated marine atmospheric environment

Abstract: The influence of Ni on the corrosion behavior of Ni‐containing weathering steel (Q415NH) was investigated under alternate dry/wet conditions. The results suggested that the addition of Ni shifted the corrosion potential of the steel to the positive direction and lowered the corrosion current density. Furthermore, the addition of Ni was in favor of the formation of a compact and homogeneous inner rust layer (composed of most α‐FeOOH and little β‐FeOOH), leading to enhanced corrosion resistance of the steel in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…It is well known that the corrosion products of WS under atmospheric corrosion are composed of a small amount of Fe 3 O 4 , α -FeOOH, γ -FeOOH and more amounts of amorphous substances (Kimura et al , 2005; Misawa et al , 1971; Suzuki et al , 1981). Among these corrosion products, α -FeOOH is electrochemically and thermodynamically stable (Yamashita et al , 1994; Cheng et al , 2014). Therefore, it is an important part of the stable rust layer of WS, which directly determines whether the rust layer is compact and protected.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the corrosion products of WS under atmospheric corrosion are composed of a small amount of Fe 3 O 4 , α -FeOOH, γ -FeOOH and more amounts of amorphous substances (Kimura et al , 2005; Misawa et al , 1971; Suzuki et al , 1981). Among these corrosion products, α -FeOOH is electrochemically and thermodynamically stable (Yamashita et al , 1994; Cheng et al , 2014). Therefore, it is an important part of the stable rust layer of WS, which directly determines whether the rust layer is compact and protected.…”
Section: Resultsmentioning
confidence: 99%
“…), totaling to a maximum added alloys of 3 to 5 wt.% (Cano et al 2018). Weathering steel is a promising alternative to carbon steel because of small addition of expensive and corrosion-resistant metals, while providing better mechanical properties (Cheng et al 2014). WS was initially designed to contain chromium (Cr) content up to 1% by weight.…”
Section: Introductionmentioning
confidence: 99%
“…By adding certain amounts of corrosion-resistant elements, a dense rust layer is formed on the steel surface, which can impede further corrosion process of the substrate to achieve improvement of the steel corrosion resistance [4][5][6][7][8] . The recent researches have suggested that addition of Cr, Cu, or P alloying elements can significantly improve the rust layer structure stability of the weathering steel, thereby improving its applicability in severe industrial and marine environments [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%